Development of the Participatory Integrated Supervision Process Affecting the Teachers’ Competencies as Classroom Research on Learning Problem-solving - Tamthitirat , Napakkanai; Jedaman , Pornchai; Khattiyanon, Thanatporn; Jantanukul, Watcharaporn (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
Educational supervision is important to the performance and behavior change in the teachers as learning management. Specific purposes to development of The participatory integrated supervision process affecting the teachers’ competencies as classroom research in learning problem-solving of the schools into a study with the participants include school directors and teachers into the collections to the data. Need assessment of supervision affecting teachers’ competencies by the highest needs was participatory self-improvement. The participatory integrated supervision process of 4th key factor affecting the teachers’ competencies in classroom research in learning problem solving, CFA associated with The participatory integrated supervision process was significant at levels of 0.01. The teachers got higher scores after training, and teachers’ competencies were at a level of excellent including the relationship between knowledge with competencies to positive relationship, and the level of satisfaction was also high. Participation in the integrated supervision process was to support learning management to be the effectiveness and supervision has been conceived as the improvement of the teaching and learning process for the ultimate benefit of the learner.